Prinsip Ibahah Sebagai Solusi Hukum Terhadap Kelemahan Prinsip Wadi'ah Dan Mudarabah Dalam Undang-Undang Perbankan Syari'ah - Khoirul Hidayah; Suwandi Suwandi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
ASEAN Free Trade Area (AFTA) and ASEAN Economic Community (AEC) in 2015 have effect to liberalization in good and services in ASEAN area. To face AEC, sharia banking must support with regulation and law assurance. The writer have argument that some incorrect principles in sharia banking law. Wadiahand mud?rabah principles do not benefit in syariah banking. Those principles untruth in Islamic sharia. There are mass deception in principles using, Islamic sharia concept are not the same with the practice. Ib?hah principle is the law solution to subtitute the wadiahand mud?rabah principles. It is general principle in economic which allowed in any way as long as not contradiction with regulation.